Toward a theology of the Septuagint : Stellenbosch Congress on the Septuagint, 2018 - Cook, Johann; Rösel, Martin (Septuagint and cognate studies series ;, 2020)
"Toward a Theology of the Septuagint: Stellenbosch Congress on the Septuagint, 2018 focuses on the question of whether it is appropriate and possible to formulate a theology of the Septuagint. Nineteen English and German essays by an international group of scholars examine Old and New Testament texts from a variety of methodological perspectives to demonstrate that such a theology is indeed possible"--